2003
DOI: 10.1002/jmv.10539
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of selective inhibition of HPV‐16 DNA amplification in cervicovaginal lavages

Abstract: HPV-16 viral load has been assessed with real-time PCR assays by measuring HPV-16 DNA and a human gene in genital samples. HPV-16 viral load measurements are thus based on the inference that inhibitors contained in samples will equally impede amplification of DNA sequences from HPV-16 and human DNA. We have previously shown that sample lysates can inhibit amplification of HPV-16 but not beta-globin DNA. In the current study, cervicovaginal lavages lysates considered adequate for PCR analysis by a qualitative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…This is the first report on the role of HPV-16 viral load in cervical HPV infection and SIL in HIV-infected women combining real-time PCR and screening for PCR inhibition. The assay we used was demonstrated to be specific for HPV-16 and does not cross-react with other HPV types (6,7,14). Several studies reported a higher quantity of HPV DNA in HIVseropositive than HIV-seronegative women but did not evaluate the impact of HIV-induced immunosuppression on HPV viral load (5,11,12,16,18).…”
mentioning
confidence: 99%
“…This is the first report on the role of HPV-16 viral load in cervical HPV infection and SIL in HIV-infected women combining real-time PCR and screening for PCR inhibition. The assay we used was demonstrated to be specific for HPV-16 and does not cross-react with other HPV types (6,7,14). Several studies reported a higher quantity of HPV DNA in HIVseropositive than HIV-seronegative women but did not evaluate the impact of HIV-induced immunosuppression on HPV viral load (5,11,12,16,18).…”
mentioning
confidence: 99%
“…One hundred forty-four HPV-16-positive samples (125 cervicovaginal lavages and 19 specimens collected using vaginal tampon) were selected for the current evaluation as described above. These samples had been screened in previous studies for the presence of inhibitors by real-time PCR using internal controls for HPV-16 and h-globin (28,31,32). Briefly, 1,000 copies of HPV-16 L1 internal control, 1,000 copies of HPV-16 E6 internal control, and 1,000 copies of h-globin internal control were amplified in separate capillaries with 2 AL specimen lysate and tested in a Light Cycler PCR and detection system (Roche Molecular Systems, Branchburg, NJ; refs.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, 1,000 copies of HPV-16 L1 internal control, 1,000 copies of HPV-16 E6 internal control, and 1,000 copies of h-globin internal control were amplified in separate capillaries with 2 AL specimen lysate and tested in a Light Cycler PCR and detection system (Roche Molecular Systems, Branchburg, NJ; refs. 28,31,32). The presence of PCR inhibitors was suspected when 1,000 copies of at least one of the internal controls generated a signal corresponding to <700 copies as explained in detail previously (31).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations